The use of selenium for controlling plant fungal diseases and insect pests - Li, Qianru; Xian, Limei; Yuan, Linxi; Lin, Zhiqing; Chen, Xiaoren; Wang, Jianjun; Li, Tao (Frontiers in Plant Science, 2023)
The selenium (Se) applications in biomedicine, agriculture, and environmental health have become great research interest in recent decades. As an essential nutrient for humans and animals, beneficial effects of Se on human health have been well documented. Although Se is not an essential element for plants, it does play important roles in improving plants’ resistances to a broad of (a)biotic stresses. This review focused on recent new findings of regulatory effects and mechanisms of Se on plant fungal diseases and insect pests. Se affects the plant disease resistance by preventing the invasion of fungal pathogens, destroying the cell membrane structure of fungal pathogens to inhibit their growth, inhibiting the extension of fungal pathogens after invasion, and changing the soil microbial community as well as functional characteristics to limit fungal pathogens invasion. Moreover, Se can be metabolized into dimethyl selenide or dimethyl diselenide to act as an insect repellent to deter pests. High levels of Se can also lead to Se poisoning to some pests, which results in higher pest mortality and lower reproduction rates. The inhibition of growth and development and the shortening of adult life span of pests would protect plants from pests or pest-induced damages. The future research perspective of Se on preventing and controlling crop pest diseases and insects will need to be addressed.